Effects of 4-lobe swirl-inducing pipe on pressure drop - George, Dickson Dungau (2008)
This thesis describes the effects of the 4-lobe swirl-inducing pipe on pressure drops for water, sand-water slurry and carboxymethyl cellulose fluids. The pressure drops were measured for two 4-lobe swirl-inducing pipe combined, one 4-lobe swirl-inducing pipe and without swirl-inducing pipe. The swirling pipe applications were installed before a bend on radius-to-diameter (R/D) ratio of 4. The pressure drops were measured on three different locations, before and after the 4-lobe swirl-inducing pipe, and after the bend.